(untitled) (Bridging Cultures, 2020)
The purpose of this brief communication is to challenge the existing notion that plain language and legal translation are incompatible, while also inviting further research. Tackling some common objections to plain language and relying on three brief examples, I posit that if we define plain language as nothing more (and nothing less) than just seeking clarity, then plain language is perfectly compatible with legal translation.